M72 - knife gate valves - MacConnell, Mark (AWWA manual ;, 2020)
"This manual presents the general practice for selection and installation of manual and automated knife gate valves for use in water and waste-water applications. This document is intended to provide information and guidance on typical knife gate valves and their intended application"--